Occurrence and distribution of entomopathogenic nematodes (Steinernematidae and Heterorhabditidae) in Morocco. Issue 10 (2nd October 2020) - Benseddik, Youssef; Boutaleb Joutei, Abdelmalek; Blenzar, Abdelali; Ezrari, Said; Molina, Carlos M.; Radouane, Nabil; Mokrini, Fouad; Tahiri, Abdessalem; Lahlali, Rachid; Dababat, Abdelfettah A.
ABSTRACT: A survey of entomopathogenic nematodes (EPN) was conducted in Morocco during 2015 and 2016 in three regions with varying topography, climate and vegetation (Meknès-El Hajeb, Ifrane and Tafilalet). EPN were isolated from 14 of 169 soil samples (8%). Molecular and morphological techniques were used for species determination. Nine samples contained heterorhabditids and five samples contained steinernematids. Eight heterorhabditids were identified as Heterorhabditis bacteriophora Poinar 1976, two steinernematids as Steinernema feltiae (Filipjev, 1934), three as belonging to the S. feltiae -group, and one as an unidentified isolate ( Heterorhabditis sp.) which gives dark burgundy colour for G. mellonella cadavers. These EPNs were collected mainly from agricultural soils rather than natural habitats, with potential adaptation to specific geography, climate and soil conditions (texture, pH and organic matter content), including six EPN isolates from heavy soils. These data demonstrate that EPN are present in Moroccan soils but at relatively low frequency, so opportunity exists to augment these populations to gain biological control benefits.